A Note on Portfolio Selection and Taxation - Penner, R. G. (Review of Economic Studies, 1964)
Journal Article A Note on Portfolio Selection and Taxation Get access R. G. Penner R. G. Penner Rochester, New York Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 1, January 1964, Pages 83–86, https://doi.org/10.2307/2295940 Published: 01 January 1964